2017
DOI: 10.1128/aac.01245-17
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Genetic Location of mcr-1 in Colistin-Resistant Escherichia coli Isolates from Humans and Retail Chicken Meat in Switzerland: Emergence of mcr-1 -Carrying IncK2 Plasmids

Abstract: We characterized the genetic environment of mcr-1 in colistin-resistant Escherichia coli strains isolated in Switzerland during 2014 to 2016 from humans (n ϭ 3) and chicken meat (n ϭ 6). Whole-genome and plasmid sequencing identified the mcr-1 gene integrated in IncX4 (of which, one strain carried the mcr-1.2 variant), IncI2, IncHI2, and novel IncK2 plasmids (overall, n ϭ 7), as well as in the bacterial chromosome (n ϭ 2) in single or duplicate copies. Our study supports the easy mobilization of mcr-1 across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…mcr-1 was originally discovered as a mobile resistance gene on the plasmid of COR bacteria (7), and it is recognized that chromosomally carried mcr-1 is very rare compared to that on the plasmids (8)(9)(10)(11)(12)(13). For instance, Li et al found that only 4% of 200 mcr-1-positive E. coli isolates from animals, food, the environment, and human fecal samples collected in China carried chromosomal mcr-1 (11).…”
Section: Resultsmentioning
confidence: 99%
“…mcr-1 was originally discovered as a mobile resistance gene on the plasmid of COR bacteria (7), and it is recognized that chromosomally carried mcr-1 is very rare compared to that on the plasmids (8)(9)(10)(11)(12)(13). For instance, Li et al found that only 4% of 200 mcr-1-positive E. coli isolates from animals, food, the environment, and human fecal samples collected in China carried chromosomal mcr-1 (11).…”
Section: Resultsmentioning
confidence: 99%
“…This IS is typically found in Actinobacillus spp. and has been recently associated with the widespread of the colistin-resistance gene mcr-1 in different genetic backgrounds [ 31 , 32 ]. However, in 9953L55, the IS Apl1 did not flank any known antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
“…5). K1 plasmids from various locations carry bla CTX-M-14 (231), and available K2 plasmids carry bla CMY-2 or its variants (223,224) or mcr-1 (232). B/O replicons have been detected by PCR in isolates carrying resistance genes, but at least some may correspond to Z-type plasmids (222), and few fully sequenced B plasmids seem to be available.…”
Section: Resistance Plasmids In the Enterobacteriaceaementioning
confidence: 99%